MEASUREMENT OF RADON (222Rn) CONCENTRATION AT HIGH ALTITUDES IN THE NORTHERN AREAS OF PAKISTAN - Shahzad, M. I.; Sher, G.; Manzoor, S.; Khan, H. A.; Khan, E. U.; Rafique, M.; Jabeen, S. (The Nucleus, 2020)
Radon (222Rn) concentration has been measured using CN-85 solid-state nuclear track detectors in the dwellings of Northern Areas of Pakistan at different altitudes. The CN-85 detectors, installed in box type radon dosimeters, were exposed for a period of one year. The average radon concentration level has been found at altitudes 3020 m, 3540 m, 3665 m and 4265 m above sea level and the 222Rn concentrations were found to be (16.4±2.5) Bq m-3, (21.7±4.8) Bq m-3, (13.8±3.2) Bq m-3 and (19.3±3.4) Bq m-3, respectively. It has been observed that there are no significant differences in the radon concentrations with different altitudes. However, differences in concentrations were observed with types of rooms attributed to better ventilation, atmospheric parameters and source of radon present in the soil. These results have been compared with radon concentration measurement found in literature. The 222Rn concentration measured in the area under study is found below the permissible level recommended by the International Commission on Radiological Protection (ICRP) for public exposure.